City Development Concepts as a Response to the Current Challenges Cities Face - Szulc, Anna; Mempel-Śnieżyk, Anna (Koncepcje rozwoju miast jako odpowiedź na współczesne wyzwania ośrodków miejskich, 2022)
Contemporary cities differ in many structural and functional respects. Each of them has its own unique endogenous conditions and various external conditions. For the authors, the starting point was to discuss the common characteristic features and main problems that contemporary cities face. The main aim of the article was to investigate potential regularities between problems/ features of the cities and the implemented city development concepts. To this end, the theoretical concepts of development used by urban centres were analysed and the examples of those implemented. Contemporary cities pursue their goals based on the guidelines resulting, among others, from the following concepts: smart city, green city, accessible city, compact city, resilient city, creative city, 15-minute city. The methods used for the research were literature review and case studies. The analysed cases confirmed the belief that the municipal authorities must identify and firmly decide which of the existing problems in the urban space have the greatest destructive effect on them. As an element that binds all the concepts of development, a common goal should be indicated i.e. the optimisation of the quality of life of residents. The added value of the paper relates to capturing the relation between the development concepts used by cities and their features/identified problems.
Biblioteka Regionalisty = Regional Journal, 2022, Nr 22, s. 116-128
Keywords: city; urban development; development challenges; urban development concepts; miasto; rozwój miast; wyzwania rozwoju; koncepcje rozwoju miast